Open Versus Minimally Invasive Spine Surgery in the Treatment of Single-Level Degenerative Lumbar Spondylolisthesis: An AO Spine Global Cross-Sectional Study - Luca Ambrosio; Sathish Muthu; Samuel K. Cho; Micheal S. Virk; Juan P. Cabrera; Patrick C. Hsieh; Andreas K. Demetriades; Stipe Ćorluka; S. Tim Yoon; Gianluca Vadalà (Neurospine)
Objective This study aims to assess global trends in the use of open surgery versus minimally invasive surgery (MIS) for the treatment of single-level L4–5 degenerative lumbar spondylolisthesis (DLS). Methods A cross-sectional online survey issued by the AO Spine Knowledge Forum Degenerative was conducted among AO Spine members between July and September 2023. Participants were presented with 3 clinical cases of L4–5 grade 1 DLS, each with varying degrees of stenosis and instability. The survey captured surgeon demographics and preferences for open versus MIS approaches. Statistical analysis, including chi-square tests and logistic regression, was performed to explore associations between surgical choices and surgeon demographics. Results A total of 943 surgeons responded, with 479 completing the survey. Open surgery was the preferred approach in all 3 cases (58.8%, 57.3%, and 42.4%, respectively), particularly in cases involving central and bilateral foraminal stenosis. MIS was the second most common choice, particularly for unilateral foraminal stenosis with mild instability (38.8%). Surgeons’ preferences varied significantly by region, age, and fellowship training, with younger and fellowship-trained surgeons more likely to prefer MIS. Conclusion The study highlights the continued predominance of open surgery for DLS, especially in complex cases, despite the growing acceptance of MIS. Significant regional and demographic variations in surgical preferences suggest the need for tailored guidelines and standardized training protocols to optimize patient outcomes. Future research should focus on the long-term efficacy of these approaches and the impact of evolving technologies on surgical decision-making.